Keteladanan Nabi sebagai Kontrol Hedonisme Kalangan Remaja Perspektif al-Qur’ān dan Ḥadīth - Adabi Dino Sweta; Rizya Oktavia; Restiana Urba Natasyah (ALSYS, 2026)
The development of digital media has changed adolescents’ lifestyles, including the increasing tendency toward a hedonistic lifestyle characterized by consumptive behavior, flexing culture, and the pursuit of social recognition through digital media. This phenomenon has the potential to influence adolescents’ character formation and shift their life orientation from meaningful values toward momentary pleasure. This study aims to analyze the exemplary conduct of Prophet Muhammad as a model for controlling hedonistic lifestyles among adolescents based on the perspectives of the Qur’an and Hadith. This study used a qualitative method with a library research approach. Data were obtained from Qur’anic verses, the Prophet’s hadiths, Qur’anic exegesis books, hadith commentary books, and scientific literature relevant to the themes of hedonism, consumptive behavior, and character education. The data were analyzed using a thematic approach and content analysis. The results showed that the Qur’an criticizes hedonistic behavior through prohibitions against isrāf, tabdhīr, and excessive life orientation toward material aspects. As an alternative, Islam offers prophetic values reflected in the exemplary conduct of Prophet Muhammad, including qanā‘ah, self-control, simplicity in life, social concern, and balance between worldly life and the hereafter. These values are relevant in shaping adolescents’ character so that they are able to face the pressures of consumptive culture and the influence of social media wisely. The conclusion of this study affirms that the exemplary conduct of Prophet Muhammad can serve as a conceptual and practical foundation for controlling adolescents’ tendency toward hedonism and forming a young generation that is characterized, moderate, and responsible in the digital era.